DEUSILITES TENUISTRIATUS SP. NOV. (ACRITARCA) EN EL PÉRMICO INFERIOR DE LA CUENCA CHACOPARANENSE (ARGENTINA) (Ameghiniana, 2014)
A new species ofthe acritarch genus Deusilites is described (D. tenuistriatus). This species, that characterizes Lower Permian strata of the Chacoparanense Basin in Argentina and Paraná Basin of Brazil, is found in assernblages dominated by continental palynomorphs. lts association with other acritarchs suggests a nearshore marine environment. A taxonomic discussion about similar genera is also presented.